Synthesis, structural and electrochemical study of graphene-based materials for lithium-oxygen batteries - Zhang, Wenyu (2015)
Due to the crisis of conventional fossil fuels, the need of new generation of green power sources is increasing nowadays. Graphene-based materials have been fervidly studied in the realm of energy storage systems because of its high flexibility, electrical conductivity and low cost.Li-O2 batteries are attracting more and more interest around the world because of their high capacity. In this work, graphene-based materials is prepared and studied for LOBs. First, a novel method is proposed to prepare bind-free graphene foams as O2 electrodes for Li-O2 batteries. The graphene foams are synthesized by electrochemical leavening of the graphite papers, followed by annealing in inert gas to control the amounts of the structural defects of the graphene foams. It was found that the structural defects were detrimental to the processes of the ORR and OER in Li-O2 batteries. The round-trip efficiencies and the cycling stabilities of the graphene foams were undermined by the structural defects. For example, the as-prepared graphene foam with a high defect level (ID/IG=0.71) depicted a round-trip efficiency of only 0.51 and a 20th-cycle discharge capacity of only 340 mAh g-1 at a current density of 100 mA g-1. By contrast, the graphene foam electrode annealed at 800 oC with ID/IG=0.07 delivered a round-trip efficiency of up to 80 % with a stable discharge voltage at ~2.8 V and a stable charge voltage below 3.8 V for 20 cycles. According to the analysis on the electrodes after 20 cycles, the structural defects led to the quickened decay of the graphene foams and the boosted formation of the side products. Besides, an electrochemical method is proposed to synthesize transition metal oxides/graphene composites. The method combines electrochemical deposition of redox active materials and exfoliation of graphene in one step. Fe2O3nanoclusters decorated graphene (Fe2O3/graphene) hybrids with controlled contents of Fe2O3 were prepared by this process. These Fe2O3/graphene hybrids were tested as O2 electrodes for Li-O2 batteries, which exhibited enhanced discharge capacities as compare that of pure graphene based O2 electrode, e.g. the Fe2O3/graphene electrode with 29.0 wt% of Fe2O3 delivered a discharge capacity of 8290 mAh g-1 as compared to 5100 mA h g-1 for pure graphene electrode. The excellent electrochemical properties of Fe2O3/graphene as O2 electrodes is ascribed to the combination of the fast kinetics of electron transport provided by the graphene sheets and the high electrocatalytic activities for O2 reduction provided by the Fe2O3. Finally, metallopolymer nanowalls were prepared through a simple wet-chemical process using reduced graphene oxides as heterogeneous nucleation aids, which also help to form conductive electron paths. The nanowalls grow vertically on graphene surface with 100 -200 nm in widths and ~ 20 nm in thickness. The Fe-based metallopolymer nanowall based electrode shows best performance as O2 cathode for Li-O2 batteries exhibiting high round-trip efficiencies and stable cycling. The electrode delivers discharge-charge capacities of 1000 mAh/g for 40 cycles and maintains round-trip efficiencies >78 % at 50 mA/g. The 1st-cycle round-trip efficiencies are 79 %, 72 % and 65 % at current densities of 50, 200 and 400 mA/g, respectively. The NMR analysis of the Fe-based metallopolymer based electrode after 40 cycles reveals slow formation of the side products of CH3CO2Li andHCO2Li. The novelties and significant progress in terms of science and technologies in the main work (Chapter 4) of this thesis are summarized as the following. In the 1st section of Chapter 4, a novel electrochemical leavening strategy followed by annealing to produce graphene foams with small amounts of defects/functionalities is developed. The correlation between the amounts of defects/functionalities of graphene and the electrochemical performance of LOBs is studied and interpreted. In the 2nd part of Chapter 4, a novel electrochemical method to synthesize Fe2O3/graphene composites is developed. This method exhibits much improved efficiencies to produce graphene-based composites in comparison to the conventional approaches. Another original contribution in the field of LOBs is that the contents of Fe2O3 in the composites are studied and correlated to the electrochemical performance of LOBs. In the 3rd section of Chapter 4, metallopolymers/graphene composites with novel morphologies are synthesized. An original strategy to improve the performance of LOBs is proposed: altering the architecture/morphologies of the electrode materials. The above-mentioned materials exhibitoutstanding properties as cathodes of LOBs in comparison to the conventional electrodes for air/oxygen batteries, e.g. precious metals/amorphous carbons, which are reported in the literatures. Therefore, the graphene-based composite materials are promising candidates for LOBs due to the low cost and high performance.